Readiness of Credentials and Medical Personnel in Implementing the Qualifications and Education of Medical Personnel According to the Elements of Assessing Staff Qualifications and Education in 10 Accreditation Standards at West Muna District Hospital - Syahril Fitrah, Muhammad; Risky, Sartini; Tasnim, Tasnim (Waluya The International Science of Health Journal, 2024)
Introduction:The Regional Unit Hospital of West Muna Regency continues to strive to improve the quality of service by preparing the implementation of qualifications and education of medical personnel. The purpose of this study was to analyze the readiness of the Hospital in implementing qualifications and readiness of medical personnel according to the assessment elements of KPS 10 accreditation standards at the Regional Unit Hospital of West Muna Regency. Method:This study uses a qualitative method with a case study design, the informants in this study were 16 people from government agencies, professional organizations, personnel, medical committees and doctors at the Muna Barat District Regional Unit Hospital. Furthermore, interviews were conducted using interview guidelines. Result:The results of this study indicate that the Regional Unit Hospital of West Muna Regency is ready to implement the qualifications and education of medical personnel according to the assessment elements of KPS 10 accreditation standards. The results of the interview found that in the five components of KPS 10 accreditation standards, namely credentials and medical personnel at the Regional Unit Hospital of West Muna Regency. Conclusion: The Muna Barat District Regional Unit Hospital is ready to implement the qualifications and education of medical personnel according to the KPS 10 accreditation standard assessment elements.